Getting More from Cross‐Functional Fairness and Product Innovativeness: Contingency Effects of Internal Resource and Conflict Management. Issue 1 (17th October 2012) - Clercq, Dirk De; Thongpapanl, Narongsak (Tek); Dimov, Dimo
<x xml:space="preserve">Abstract</x> This research investigates how organizations' internal resource and conflict management influence the relationship between cross‐functional fairness and product innovativeness. It considers two contextual dimensions of both internal resource management (job rotation and internal rivalry) and conflict‐handling mechanisms (integrating and avoiding) as key components of the firm's ability to convert fair interactions, across departments, into product innovativeness. The tests of the study's hypotheses, based on a sample of more than 200 Canadian‐based firms, confirm that the cross‐functional fairness–product innovativeness relationship is amplified at higher levels of job rotation and integrative conflict handling but suppressed at higher levels of internal rivalry and avoidance of conflict handling. The authors discuss the study's implications and future research directions.